The Influence Of Educational Background, Courtesy Personality And Internal Control On The Quality Of Financial Statements (Study on Islamic Boarding Schools of West Tanjung Jabung Regency) - Victor Diwantara; Anzu Elvia Zahara; Zul Febri (Citakonsultindo, 2026)
This research is motivated by the phenomenon that most Islamic boarding schools in Tanjung Jabung Barat Regency still use simple financial records that have not referred to the Islamic Boarding School Accounting Guidelines. This poses challenges in producing quality, accountable, and standard financial reports. Factors that are suspected to affect the quality of financial statements include educational background, courtesy personality, and internal control. This type of research is quantitative research with a field approach. Primary data was obtained through the distribution of questionnaires to 31 respondents, namely administrators and treasurers at eight Islamic boarding schools in West Tanjung Jabung Regency. Data analysis uses multiple linear regression with the help of SPSS applications. The results of the study show that partially educational background and courtesy personality have no effect on the quality of financial statements. On the other hand, internal control affects the quality of financial statements. Simultaneously, educational background, courtesy personality and internal control have no effect on the quality of financial statements.